Separator for electrochemical device

By using a porous polyolefin substrate and a porous inorganic coating containing boehmite in separators for electrochemical devices, the problems of thermal shrinkage and insufficient bonding strength of separators at high temperatures are solved, achieving higher heat resistance. and stability.

CN119343825APending Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480002928.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-07
Filing Date
2024-03-06
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The separators of existing electrochemical devices exhibit heat shrinking behavior at high temperatures, resulting in a short circuit between the positive electrode and the negative electrode, and insufficient adhesion strength to the porous inorganic coating, affecting safety and stability.

Method used

A porous polyolefin substrate is used as the separator substrate, which contains a cross-linked polyolefin resin and a silicon-containing organic group grafted onto the polyolefin chain, and a porous inorganic coating containing boehmite is coated on the surface to Improve bond strength and wettability.

Benefits of technology

The bonding strength between the separator substrate and the porous coating and the wettability of the separator substrate are significantly improved, the heat resistance and stability of the electrochemical device are improved, and the risk of short circuit is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005176700750000241
    Figure BDA0005176700750000241
  • Figure BDA0005176700750000261
    Figure BDA0005176700750000261
Patent Text Reader

Abstract

The present disclosure relates to a separator and an electrochemical device including the same, and the separator of the present disclosure includes a porous polyolefin substrate having improved wettability and a porous coating layer having high adhesion to the porous polyolefin substrate. Specifically, the separator includes a porous polyolefin substrate and a porous coating layer on at least one surface of the porous polyolefin substrate, in which the porous polyolefin substrate includes a cross-linked polyolefin resin, in which the cross-linked polyolefin resin includes a silicon-containing organic group grafted onto a polyolefin chain, wherein the porous coating comprises inorganic particles and a binder polymer, and wherein the inorganic particles comprise boehmite (AlO (OH)).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the same.

[0002] This application claims priority to Korean Patent Application No. 2023-0030218 filed in Korea on March 7, 2023, the disclosure of which is incorporated herein by reference. Background Art

[0003] Secondary batteries including lithium ion secondary batteries are widely used as power sources for portable electronic devices such as notebook computers, mobile phones, digital cameras, video cameras, etc. Recently, these batteries are being used in a wide range of applications including vehicles due to their high energy density.

[0004] Lithium secondary batteries have much higher operating voltage and energy density than traditional batteries using aqueous electrolyte solutions (e.g., Ni-MH batteries, Ni-Cd batteries, lead-acid batteries), and due to these advantages, lithium secondary batteries are gaining a lot of attention. However, lithium-ion batteries have safety-related fire and explosion risks due to the use of organic electrolytes, and require time-consuming, labor-intensive and picky manufacturing processes. Recently, lithium-ion polymer batteries, which have evolved from lithium-ion batteries, are regarded as one of the next generation of batteries, but still have lower battery capacity than lithium-ion batteries, and insufficient discharge capacity, especially at low temperatures, and are therefore in urgent need of improvement.

[0005] It is very important to evaluate the stability of electrochemical devices and ensure safety. In terms of the safety characteristics of electrochemical devices, there is a great concern about explosion when thermal runaway occurs due to overheating or the separator is punctured. In particular, polyolefin-based separator substrates, which are generally used as separators for electrochemical devices, exhibit severe thermal shrinkage behavior at temperatures of 100°C or higher due to material properties and process properties including stretching, resulting in a short circuit between the positive and negative electrodes.

[0006] In order to solve the safety problem of electrochemical devices, a separator has been proposed in which a separator substrate having pores has a porous inorganic coating on at least one surface thereof, and the porous inorganic coating comprises a mixture of excess inorganic particles and a binder polymer, and further, enhanced stability is continuously required. For example, enhanced bonding strength is required at the interface between the porous inorganic coating comprising excess inorganic particles and the separator substrate. Summary of the invention

[0007] Technical issues

[0008] The present disclosure is intended to provide a separator,

[0009] The separator has enhanced wettability of a separator substrate and improved bonding strength between the separator substrate and a porous inorganic coating layer including excess inorganic particles.

[0010] Therefore, the present disclosure aims to provide an electrochemical device having improved stability and high resistance characteristics.

[0011] Technical Solution

[0012] In order to solve the above problems,

[0013] According to one aspect of the present disclosure, a separator of the following embodiment is provided.

[0014] A separator substrate according to a first embodiment includes,

[0015] a porous polyolefin substrate and a porous coating on at least one surface of the porous polyolefin substrate,

[0016] wherein the porous polyolefin substrate comprises,

[0017] Cross-linked polyolefin resin,

[0018] wherein the cross-linked polyolefin resin comprises silicon-containing organic groups grafted onto polyolefin chains,

[0019] The porous coating comprises:

[0020] Inorganic particles and binder polymers,

[0021] And wherein the inorganic particles comprise boehmite (AlO(OH)).

[0022] According to a second embodiment, in the first embodiment,

[0023] The porous polyolefin substrate may have

[0024] 3% to 80% gel fraction,

[0025] And the standard deviation (Δd) of the thickness measured at at least 100 random points may be 0.5 μm or less.

[0026] According to a third embodiment, in the first embodiment or the second embodiment,

[0027] The adhesive strength between the porous polyolefin substrate and the porous coating layer may be 50 gf or more.

[0028] According to a fourth embodiment, in any one of the first to third embodiments,

[0029] The bonding strength between the porous polyolefin substrate and the porous coating layer may be 70 gf to 95 gf.

[0030] According to a fifth embodiment, in any one of the first to fourth embodiments,

[0031] Based on the total weight of inorganic particles,

[0032] The amount of boehmite may be 80 wt% or more.

[0033] According to a sixth embodiment, in the fifth embodiment,

[0034] The silicon-containing organic group may be a residue from a vinyl-containing silane compound,

[0035] And the vinyl-containing silane compound may include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, (3-methacryloxypropyl)trimethoxysilane, (3-methacryloxypropyl)triethoxysilane, vinylmethyldimethoxysilane, vinyl-tri(2-methoxyethoxy)silane, vinylmethyldiethoxysilane, or a mixture of two or more thereof.

[0036] According to a seventh embodiment, in any one of the first to sixth embodiments,

[0037] The porous polyolefin substrate may also contain chromium (Cr).

[0038] According to an eighth embodiment, in any one of the first to seventh embodiments,

[0039] The amount of chromium may be from 0.1 ppm to 20 ppm.

[0040] According to a ninth embodiment, in any one of the first to eighth embodiments,

[0041] The crosslinked structure in the crosslinked polyolefin resin may include a structure derived as a result of a free radical polymerization reaction between vinyl groups mediated by a thermal initiator.

[0042] According to a tenth embodiment, in any one of the first to ninth embodiments,

[0043] The thermal initiator may include a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

[0044] According to another aspect of the present disclosure, an electrochemical device according to the following embodiment is provided.

[0045] An electrochemical device according to an eleventh embodiment includes

[0046] A positive electrode, a negative electrode, and the separator according to any one of the first to tenth embodiments between the positive electrode and the negative electrode.

[0047] Beneficial Effects

[0048] The separator according to one embodiment of the present disclosure may exhibit high adhesive strength between the porous polyolefin substrate and the porous coating layer and high wettability of the separator substrate.

[0049] In particular, the porous polyolefin substrate as a separator substrate may include multiple cross-linked structures in the polyolefin chain to achieve improved thickness uniformity and heat resistance, and may include a silicon-containing organic group grafted to the polyolefin chain to achieve improved wettability with the electrolyte and improved adhesion strength between the porous polyolefin substrate and the porous coating. In addition, the porous coating may include boehmite as an inorganic particle to achieve improved adhesion strength between the porous polyolefin substrate and the porous coating.

[0050] Therefore, operation stability, such as heat resistance characteristics, in an electrochemical device including a separator using the separator substrate may be improved, but the mechanism of the present disclosure is not limited thereto. DETAILED DESCRIPTION

[0051] Hereinafter, the present disclosure will be described in detail.

[0052] The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the same. In the present disclosure, an electrochemical device is a device that converts chemical energy into electrical energy through an electrochemical reaction, and is a concept covering primary batteries and secondary batteries. Secondary batteries can be recharged, and are a concept covering lithium-ion batteries, nickel-cadmium batteries, nickel-hydrogen batteries, etc.

[0053] In one embodiment of the present disclosure, the separator for an electrochemical device may be a Safety Reinforced Separator (SRS), a Ceramic Coated Separator (CCS), or a separator formed by any other known manufacturing method.

[0054] In one embodiment of the present disclosure, SRS is gaining attention because a liquid binder resin (i.e., a solution containing the binder resin) is generally used in the manufacturing method to form a porous coating, and the liquid binder resin is infiltrated into the porous separator substrate, thereby improving the bonding strength between the separator substrate and the porous coating. However, there is still a need to overcome the weak bonding strength between the separator substrate and the liquid binder resin due to the hydrophobic properties of the separator substrate as generally exhibited, or the inherent low bonding strength in the porous coating due to the large amount of inorganic particles contained in the porous coating.

[0055] In another embodiment of the present disclosure, as is known, fundamentally, the bonding strength between the separator substrate and the porous coating of CCS is lower than that of SRS because the absolute amount of binder resin used in the manufacturing method is generally lower than that of SRS, and a particulate binder resin is used when forming the porous coating.

[0056] According to one aspect of the present disclosure, the manufacturing method is not limited to a specific one and may include an SRS manufacturing method, a CCS manufacturing method, or any other known manufacturing method to provide a separator having high bonding strength between a separator substrate and a porous coating layer.

[0057] To this end, a separator for an electrochemical device according to one aspect of the present disclosure includes a separator substrate having improved heat resistance and wettability as described below and a porous coating layer having high adhesive strength with the separator substrate.

[0058] Specifically, the separator includes a porous polyolefin substrate and a porous coating layer on at least one surface of the porous polyolefin substrate.

[0059] wherein the porous polyolefin substrate comprises a cross-linked polyolefin resin, the cross-linked polyolefin resin comprises silicon-containing organic groups grafted onto polyolefin chains, and

[0060] The porous coating layer includes inorganic particles and a binder polymer, and the inorganic particles include boehmite (AlO(OH)).

[0061] According to one embodiment of the present disclosure, the porous polyolefin substrate may include a cross-linked polyolefin resin and chromium (Cr).

[0062] First, a porous polyolefin substrate as a separator substrate having improved heat resistance and wettability will be described in detail.

[0063] Porous polyolefin substrate

[0064] The porous polyolefin substrate is a separator substrate for an electrochemical device comprising a cross-linked polyolefin resin, and the cross-linked polyolefin resin comprises a silicon-containing organic group grafted onto a polyolefin chain.

[0065] In one embodiment of the present disclosure, the cross-linked polyolefin resin may include chromium (Cr) derived from a chromium (Cr)-containing catalyst used to produce polyolefin, but the present disclosure is not limited thereto.

[0066] In one embodiment of the present disclosure, in the porous polyolefin substrate, the gel fraction may be 3% to 80%.

[0067] In one embodiment of the present disclosure, in the porous polyolefin substrate, a standard deviation Δd of thickness measured at at least randomly 100 points may be 0.5 μm or less.

[0068] In another embodiment of the present disclosure, in the porous polyolefin substrate, the gel fraction may be 3% to 80%, and the standard deviation Δd of thickness measured at least at random 100 points may be 0.5 μm or less.

[0069] In one embodiment of the present disclosure, in the porous polyolefin substrate, every 1m 2 The number of spots whose long sides have a length of 50 μm or more may be 10 or less.

[0070] In another embodiment of the present disclosure, in the porous polyolefin substrate, the gel fraction may be 3% to 80%, the standard deviation Δd of the thickness measured at at least 100 random points may be 0.5 or less, and the thickness per 1 m 2 The number of spots whose long sides have a length of 50 μm or more may be 10 or less.

[0071] According to one embodiment of the present disclosure, the polyolefin resin is not limited to a specific monomer and can be made of any type of monomer used for the porous separator substrate. For example, the polyolefin resin may include: a homopolymer of a monomer selected from polyethylene, polypropylene, polybutene, polypentene, polyhexene, polyoctene, ethylene, propylene, butene, pentene, 4-methylpentene, hexene and octene; a copolymer of two or more thereof; or a mixture thereof, but is not limited thereto.

[0072] In the present specification, in the method for manufacturing a porous polyolefin substrate, as described below, the polyolefin resin includes a polyolefin resin produced using an olefin polymerization catalyst including chromium (Cr), and thus the porous polyolefin substrate may include chromium (Cr). Specifically, the porous polyolefin substrate includes chromium as a residue of a chromium catalyst used in the polymerization of the polyolefin resin.

[0073] In one embodiment of the present disclosure, the olefin polymerization catalyst containing chromium may include, for example, chromium oxide; and a carrier for supporting the chromium oxide, and the carrier may include, for example, at least one of silica, titania, alumina, zirconia or aluminum phosphate, but the present disclosure is not limited thereto.

[0074] In one embodiment of the present disclosure, the amount of chromium included in the porous polyolefin substrate may be, for example, 0.1 ppm to 20 ppm, 1 ppm to 10 ppm, or 5 ppm to 10 ppm, but is not limited thereto. The amount of chromium in the porous polyolefin substrate may be, for example, a value measured using an inductively coupled plasma mass spectrometer (ICP-MS). When the amount of chromium included in the porous polyolefin substrate is within the above range, this may have a beneficial effect on the number of vinyl groups in the polyolefin resin before crosslinking and the degree of crosslinking of the crosslinked polyolefin resin produced using the same, but the present disclosure is not limited thereto.

[0075] According to one embodiment of the present disclosure, the polyolefin resin produced using the olefin polymerization catalyst containing chromium contains a large number of terminal vinyl groups in an active state, which can be cross-linked by a thermal initiator contained in a coating solution in a subsequent process. Therefore, the porous polyolefin substrate can contain a polyolefin resin having a plurality of cross-linked structures between polyolefin chains through a cross-linking reaction caused by a thermal initiator.

[0076] In addition, according to one embodiment of the present disclosure, the polyolefin resin produced using the olefin polymerization catalyst containing chromium contains a large number of terminal vinyl groups in an active state, which provides a grafting position for the vinyl-containing silane compound contained in the coating solution in the subsequent process. Therefore, the porous polyolefin substrate can contain a silicon-containing organic group by grafting a plurality of vinyl-containing silane compounds via the terminal vinyl groups.

[0077] In one embodiment of the present disclosure, silicon-containing organic groups grafted onto polyolefin chains may be present on a surface portion of the porous polyolefin substrate, thereby adding polarity to the surface of the porous polyolefin substrate and improving chemical affinity with inorganic particles in the porous coating layer on the porous polyolefin substrate.

[0078] In this specification, "crosslinked polyolefin resin" refers to a polyolefin resin in which vinyl groups present in the chains of the polyolefin resin used as a raw material of the porous polyolefin substrate are activated by an initiation reaction to form a crosslinked structure in and / or between chains of the polyolefin resin.

[0079] Specifically, the cross-linked polyolefin resin may include a cross-linked structure in which a vinyl group present at a terminal in a polyolefin chain is activated by a thermal initiator to form a free radical, which then reacts with a free radical in a polyolefin chain of another molecule and / or a free radical at another terminal in a polyolefin chain of the same molecule to form a C(Sp) 2 )-C(Sp 2 )key.

[0080] Furthermore, in one embodiment of the present disclosure, the "silicon-containing organic group grafted onto the polyolefin chain" may be a residue from the vinyl-containing silane compound after the vinyl groups present in the polyolefin resin chain used as a raw material for the porous polyolefin substrate and the vinyl groups in the vinyl-containing silane compound are activated by an initiation reaction to form a new covalent bond at the activated site.

[0081] In one embodiment of the present disclosure, the silicon-containing organic group may be an organic residue from a vinyl-containing silane compound, and the vinyl-containing silane compound may include, for example, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, (3-methacryloxypropyl)trimethoxysilane, (3-methacryloxypropyl)triethoxysilane, vinylmethyldimethoxysilane, vinyl-tri(2-methoxyethoxy)silane, vinylmethyldiethoxysilane, or a mixture of two or more thereof, but the present disclosure is not limited thereto.

[0082] In one embodiment of the present disclosure, the cross-linked polyolefin resin may not include a terminal vinyl group, or may include a smaller number of terminal vinyl groups than the number of terminal vinyl groups present in the polyolefin resin before cross-linking.

[0083] In a similar aspect, the cross-linked polyolefin resin may contain C(Sp) less than that contained in the polyolefin resin before cross-linking. 2 )-C(Sp 2 ) keys, a greater number of C(Sp 2 )-C(Sp 2 )key.

[0084] In one embodiment of the present disclosure, when using a nuclear magnetic resonance spectrometer (Bruker 500NMR, 14.1telsa) to determine the number of functional groups from the 1H-NMR spectrum results, the polyolefin resin produced using an olefin polymerization catalyst comprising chromium can include 100 or more, 200 or more, 300 or more, 400 or more, 500 or more, 600 or more, 700 or more, 800 or more, 900 or more, or 950 or more terminal vinyl groups per 1,000,000 carbons. The upper limit of the number of terminal vinyl groups can be 1,500 or less, or 1,000 or less within the above range, but is not limited thereto.

[0085] Therefore, in one embodiment of the present disclosure, the number of terminal vinyl groups of the polyolefin resin before crosslinking may be, for example, 100 or more, 200 or more, 300 or more, 400 or more, 500 or more, 600 or more, 700 or more, 800 or more, 900 or more, or 950 or more per 1,000,000 carbons.

[0086] In another embodiment of the present disclosure, when the porous polyolefin substrate contains a polyolefin resin produced using a catalyst other than an olefin polymerization catalyst containing chromium together, the number of terminal vinyl groups of the polyolefin resin before crosslinking and the amount of terminal vinyl groups of the polyolefin resin before crosslinking are preferably measured based on the number of terminal vinyl groups and the amount of terminal vinyl groups of the entire polyolefin resin.

[0087] As described above, the crosslinked structure in the crosslinked polyolefin resin includes a structure derived as a result of a free radical polymerization reaction between vinyl groups mediated by a thermal initiator.

[0088] In one embodiment of the present disclosure, thermal initiators may include, but are not limited to, any type of initiator that activates vinyl groups present in polyolefin chains to form free radicals. Specifically, thermal initiators may include, but are not limited to, any type of initiator that activates terminal vinyl groups present in polyolefin chains to form free radicals. Thermal initiators may include, for example, peroxide-based compounds, persulfate-based compounds, azo-based compounds, or mixtures thereof.

[0089] The peroxide-based compound may include, for example, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (DHBP), benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, dicumyl peroxide, cumyl peroxide, hydrogen peroxide, or a mixture of two or more thereof, but is not limited thereto.

[0090] Persulfate-based compounds may include, but are not limited to, compounds containing peroxymonosulfate ions (SO 5 2- ) or peroxydisulfate (S 2 O 8 2- ) as an anion. Persulfate-based compounds may include, for example, sodium persulfate (Na 2 SO 5 ), potassium persulfate (KHSO 5 ), sodium persulfate (Na 2 S 2 O 8 ), ammonium persulfate ((NH 4 ) 2 S 2 O 8 ), potassium persulfate (K 2 S 2 O 8 ), or a mixture of two or more thereof, but not limited thereto.

[0091] The azo-based compound may include, for example, 2,2′-azobis(2-methylpropionitrile) (AIBN), but is not limited thereto.

[0092] In one embodiment of the present disclosure, the porous polyolefin substrate may further include a polyolefin resin produced by another type of olefin polymerization catalyst in addition to the polyolefin resin produced by the olefin polymerization catalyst containing chromium as described above.

[0093] Another type of olefin polymerization catalyst may be, for example, an olefin polymerization catalyst comprising at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr) or vanadium (V). Therefore, the separator substrate may also comprise, for example, at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr) or vanadium (V).

[0094] In one embodiment of the present disclosure, the additional type of olefin polymerization catalyst may include, for example, a metallocene catalyst, a Ziegler-Natta catalyst, or a mixture thereof, but the present disclosure is not limited thereto.

[0095] In this specification, a polyolefin resin produced using an olefin polymerization catalyst containing chromium may be referred to as a "Cr type polyolefin", and a polyolefin resin produced using another type of olefin polymerization catalyst may be referred to as a "ZT type polyolefin".

[0096] In one embodiment of the present disclosure, when the porous polyolefin substrate comprises a polyolefin resin produced using an olefin polymerization catalyst containing chromium and a polyolefin resin produced using another type of olefin polymerization catalyst, the weight ratio of the Cr type polyolefin to the ZT type polyolefin may be, for example, 1:9 to 9:1, specifically 2:8 to 8:2, 3:7 to 7:3, or 5:5, but is not limited thereto. When the separator substrate comprises the Cr type polyolefin and the ZT type polyolefin together, the molecular weight of the separator substrate may be increased by the ZT type polyolefin having a high molecular weight, but the present disclosure is not limited thereto.

[0097] In one embodiment of the present disclosure, in addition to polyolefin, as a raw material of the separator substrate, the separator may also include, for example, at least one type of polymer resin in the following: polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, or polyethylene naphthalate. In addition, the porous polyolefin substrate may include a nonwoven fabric, a porous polymer film, or a stack of two or more thereof, but is not particularly limited thereto.

[0098] In one embodiment of the present disclosure, as described below, the porous polyolefin substrate comprises a polyolefin resin produced using an olefin polymerization catalyst containing chromium, and in the process of manufacturing the separator substrate, when the polyolefin sheet derived from the polyolefin resin is heat-set, a cross-linked structure is formed in the chain and / or between the chains in the polyolefin resin by a free radical polymerization reaction mediated by a thermal initiator, thereby improving the thickness uniformity and heat resistance of the porous polyolefin substrate and improving the appearance characteristics of the porous polyolefin substrate. In addition, when the polyolefin sheet derived from the polyolefin resin is heat-set, a vinyl-containing silane compound is grafted, thereby improving the wettability of the porous polyolefin substrate, but the mechanism of the present disclosure is not limited thereto.

[0099] According to one embodiment of the present disclosure, the gel fraction of the porous polyolefin substrate is 3% to 80%. This feature can be found in a porous polyolefin substrate containing a polyolefin resin with a high degree of crosslinking, but the features of the present disclosure are not limited thereto. The gel fraction of the porous polyolefin substrate can be, for example, 3% to 70%, 3% to 60%, 3% to 50%, 3% to 45%, 3% to 40%, 3% to 30%, 3% to 20%, or 3% to 10%.

[0100] As described above, the polyolefin resin is characterized by showing a high degree of crosslinking due to the crosslinking structure in and / or between polyolefin chains. Therefore, the polyolefin resin before crosslinking is dissolved in a benzene-based solvent, while the crosslinked polyolefin resin is not dissolved in a benzene-based solvent, so that the gel fraction can be measured.

[0101] In this specification, the gel fraction can be measured by the following method. First, 0.2 g of the separator substrate sample to be measured is placed in a 120-mesh stainless steel sieve, then extracted in trichlorobenzene at 100°C for 12 hours, and dried in a vacuum oven at 100°C for 12 hours. Subsequently, the weight of the sample remaining in the stainless steel sieve is measured, and the gel fraction is measured according to the following equation. The gel fraction can be the average of the measured values ​​of 3 samples to improve the measurement accuracy.

[0102] Gel fraction (%) = {(remaining sample weight g) / 0.2 g} × 100

[0103] In one embodiment of the present disclosure, a standard deviation Δd of thickness measured at at least 100 random points of the porous polyolefin substrate is 0.5 μm or less. Therefore, the separator substrate may have high thickness uniformity.

[0104] In one embodiment of the present disclosure, the standard deviation Δd of the thickness measured at least at random 100 points of the porous polyolefin substrate may be, for example, 0.5 μm or less, 0.45 μm or less, 0.40 μm or less, 0.35 μm or less, 0.3 μm or less, or 0.25 μm or less. As the standard deviation approaches 0, the thickness uniformity improves, and the lower limit of the standard deviation of the thickness may be 0.

[0105] The thickness of the separator substrate can be measured by a method for measuring the thickness of the separator substrate, for example, a value measured by a scanning electron microscope (SEM) image analysis of the separator substrate or a known thickness measuring instrument. The thickness measuring instrument may include, for example, VL-50S-B (Mitutoyo), but is not limited thereto.

[0106] Generally, in the manufacture of a separator substrate, when a polymer resin as a raw material and additives such as a diluent and a cross-linking agent are all fed into an extruder at once to cause a reaction, a side reaction occurs in the extruder, and due to poor mixing between the raw materials, spots having a brightness difference compared to other areas are observed on the surface of the separator substrate due to unmelted raw materials.

[0107] In this specification, "spots" refer to areas having a white spot shape due to higher brightness and lower transparency than surrounding areas on the surface of the separator substrate.

[0108] In one embodiment of the present disclosure, the number of spots may be evaluated by observation with the naked eye or with a microscope such as SEM.

[0109] According to one embodiment of the present disclosure, by feeding a polyolefin resin as a raw material, forming a polyolefin sheet, and adding a thermal initiator and a vinyl-containing silane compound, a porous polyolefin substrate can have fewer spots and almost no defects in appearance. 2 The number of spots with a long side length of 50 μm or more may be 10 or less. Specifically, under the above conditions, the number of spots may be 0 to 7, 0 to 5, 0 to 3, or 0. When the number of spots is within the above range, it may be beneficial to prevent non-coating and short circuits in the battery caused by defects in appearance during subsequent ceramic coating.

[0110] In another embodiment of the present disclosure, the thickness of the porous polyolefin substrate may be, for example, 4 μm to 20 μm. When the thickness of the porous polyolefin substrate is within the above range, this may have a beneficial effect on the conductive barrier function and resistance of the separator, but the present disclosure is not limited thereto.

[0111] In one embodiment of the present disclosure, the weight average molecular weight Mw of the polyolefin resin contained in the porous polyolefin substrate may be, for example, in the range of 100,000 to 5,000,000. When the weight average molecular weight of the polyolefin resin is within the above range, this may have a beneficial effect on the mechanical properties and shutdown properties of the separator substrate, but the present disclosure is not limited thereto.

[0112] In the present specification, the weight average molecular weight Mw of the polyolefin resin may be measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions.

[0113] -Column: PL Olexis (Polymer Laboratories)

[0114] -Solvent: Trichlorobenzene (TCB)

[0115] -Flow rate: 1.0ml / min

[0116] -Sample concentration: 1.0mg / ml

[0117] -Injection volume: 200μL

[0118] - Column temperature: 160℃

[0119] -Detector: Agilent high temperature RI detector

[0120] -Standard: Polystyrene (cubic polynomial fit)

[0121] In one embodiment of the present disclosure, the porous polyolefin substrate may have a structure including a plurality of micropores, for example, the average pore size may be 0.01 μm to 0.10 μm, and the porosity may be 30% to 70%. When the average pore size and porosity of the porous polyolefin substrate are within the above ranges, this may have a beneficial effect on the ion permeability and mechanical strength of the separator using the same, but the present disclosure is not limited thereto.

[0122] In one embodiment of the present disclosure, the porous polyolefin substrate may have high heat resistance. For example, the fracture temperature of the porous polyolefin substrate may be 155°C or higher. For example, the fracture temperature of the porous polyolefin substrate may be 160°C or higher, 170°C or higher, 180°C or higher, 190°C or higher, 195°C or higher, and may also be 200°C or higher. As the fracture temperature of the porous polyolefin substrate is higher, the porous polyolefin substrate has heat resistance, and the upper limit of the fracture temperature of the porous polyolefin substrate may not be limited to a specific range, and may be, for example, 500°C or lower, 450°C or lower, 350°C or lower, or 300°C or lower.

[0123] In the present specification, the fracture temperature of the porous polyolefin substrate can be measured using a thermal mechanical analyzer (TMA) by applying a load of 0.01N to the porous polyolefin substrate sample to be measured, observing the degree of deformation while increasing the temperature at a rate of 5°C / min, and as the temperature increases, the porous polyolefin substrate shrinks and expands, and the temperature at the time of rupture can be measured as the fracture temperature.

[0124] In one embodiment of the present disclosure, the porous polyolefin substrate including silicon-containing organic groups grafted onto the polyolefin chains as described above may have improved wettability.

[0125] In one embodiment of the present disclosure, the "wettability" of the porous polyolefin substrate refers to the degree of wetting by the electrolyte, and can be evaluated by a method generally used to evaluate how much electrolyte solution is permeated, for example, it can be evaluated by dropping a predetermined amount of electrolyte solution to the porous polyolefin substrate and measuring the area to which the electrolyte solution diffuses after a predetermined time. It can be evaluated that the wider the area where the electrolyte solution drop spreads for the same time, the higher the wettability with the electrolyte solution.

[0126] The porous polyolefin substrate comprises a polyolefin resin produced using an olefin polymerization catalyst containing chromium, wherein when an oriented polyolefin sheet from the polyolefin resin is heat-set, a cross-linked structure is formed between polyolefin chains by using a thermal initiator and a vinyl-containing silane compound and the cross-linked structure comprises a grafted silicon-containing organic group, thereby improving appearance characteristics, thickness uniformity, heat resistance and wettability, but the present disclosure is not limited thereto.

[0127] Subsequently, the porous coating layer having high adhesive strength with the above-mentioned porous polyolefin substrate will be described in detail.

[0128] Porous coating

[0129] The porous coating layer contains a binder resin and inorganic particles, and has a plurality of micropores inside in which the micropores are connected to each other, and has a porous layer structure that allows air or liquid to flow from one side to the opposite side.

[0130] In one embodiment of the present disclosure, the porous coating layer may have a porous structure generated by pores corresponding to the voids (interstitial volume) between the inorganic particles. The pore size or porosity (volume ratio of pores) may be adjusted according to the particle size and particle size distribution. This structure may improve resistance to metal impurities present in the electrode and inhibit shrinkage of the porous polyolefin substrate, thereby improving the safety of the electrochemical device.

[0131] In one embodiment of the present disclosure, the porous coating may include: a plurality of nodes comprising inorganic particles and a binder polymer covering at least a portion of the surface of the inorganic particles; and at least one linear filament formed by the binder polymer of the node, wherein the filament has a node connection portion extending from the node and connecting the node to another node, and the node connection portion has a three-dimensional network structure formed by interconnecting the filaments derived from the binder polymer.

[0132] In one embodiment of the present disclosure, as described above, the porous coating layer may be formed by a safety reinforced separator (SRS) manufacturing method, a ceramic coated separator (CCS) manufacturing method, or any other known manufacturing method.

[0133] As described above, according to one embodiment of the present disclosure, the porous polyolefin substrate may include a silicon-containing organic group grafted onto the polyolefin chain, thereby improving wettability. In particular, the silicon-containing organic group grafted onto the polyolefin chain may be present on the surface portion of the porous polyolefin substrate, thereby increasing polarity to the surface of the porous polyolefin substrate and improving chemical affinity with inorganic particles in the porous coating on the porous polyolefin substrate.

[0134] According to one aspect of the present disclosure, a porous coating having improved adhesion strength with a porous polyolefin substrate having improved wettability as described above can achieve outstanding characteristics of a separator without being limited to a method for manufacturing the separator, and can improve characteristics of an electrochemical device using the same.

[0135] For this purpose, the porous coating layer contains boehmite (AlO(OH)) as inorganic particles.

[0136] According to one embodiment of the present disclosure, the aluminum-containing inorganic particles may have high adhesive strength with the porous polyolefin substrate of the present disclosure due to the -OH functional group of boehmite, but the present disclosure is not limited thereto.

[0137] According to one embodiment of the present disclosure, the bonding strength between the porous polyolefin substrate and the porous coating of the separator can be, for example, 50gf / 15mm or higher. Specifically, the bonding strength between the porous polyolefin substrate and the porous coating can be 50gf / 15mm to 100gf / 15mm, 50gf / 15mm to 95gf / 15mm, 55gf / 15mm to 95gf / 15mm, 60gf / 15mm to 95gf / 15mm, 65gf / 15mm to 95gf / 15mm, 70gf / 15mm to 95gf / 15mm, 75gf / 15mm to 90gf / 15mm, or 80gf / 15mm to 85gf / 15mm. When the bonding strength between the porous polyolefin substrate and the porous coating is within the above range, it can be beneficial to improve the performance of the electrochemical device using the separator, but the present disclosure is not limited thereto.

[0138] In the present specification, the adhesive strength between the porous polyolefin substrate and the porous coating layer can be measured by a method generally used to measure the peel strength between the porous polyolefin substrate and the porous coating layer, for example, it can be measured by the following method. A double-sided adhesive tape is attached to a glass plate, and a target separator cut to a size of 15 mm×100 mm is attached so that the surface of the porous coating layer adheres to the adhesive tape. Subsequently, the end of the attached separator is mounted on a UTM instrument, and a force is applied at 180° at a measuring rate of 300 mm / min to measure the force required to peel the porous coating layer from the separator substrate. In this case, the UTM instrument used is not limited to a specific type, and may include, for example, a LLOYD Instrument LF Plus.

[0139] In one embodiment of the present disclosure, in order to show high bonding strength with the separator substrate, the porous coating layer may contain boehmite (AlO (OH)) as inorganic particles, and specifically, based on the total weight of the inorganic particles contained in the porous coating layer, the amount of boehmite may be, for example, 80 wt% or more. More specifically, based on the total weight of the inorganic particles contained in the porous coating layer, the amount of boehmite may be, for example, 80 wt% to 100 wt%, 85 wt% to 99 wt%, 90 wt% to 95 wt%, 95 wt% to 99 wt%, or 95 wt% to 100 wt%, but the present disclosure is not limited thereto.

[0140] In another embodiment of the present disclosure, the porous coating layer may further include inorganic particles generally used in porous coating layers as inorganic particles in addition to boehmite without hindering the purpose of the present disclosure.

[0141] The inorganic particles that may be included are not limited to a specific type, and may include any type of electrochemically stable inorganic particles. That is, the inorganic particles that may be included in the present disclosure are not limited to a specific type, and may include any type of inorganic particles that are electrochemically stable. + Any type of inorganic particles that do not undergo oxidation and / or reduction reactions within a dielectric constant range of 0 V to 5 V. In particular, when high dielectric constant inorganic particles are also used as inorganic particles, it can help to increase the degree of dissociation of electrolyte salts (e.g., lithium salts) in liquid electrolytes, thereby improving the ionic conductivity of electrolyte solutions.

[0142] In one embodiment of the present disclosure, specifically, the inorganic particles that may also be included may include aluminum oxide (Al 2 O 3 ), aluminum hydroxide (Al(OH) 3 ), silicon dioxide (SiO 2 ), titanium dioxide (TiO 2 ), magnesium oxide (MgO), magnesium hydroxide (Mg(OH) 2 ), zinc oxide (ZnO), barium titanate (BaTiO), aluminum nitride (AlN), boron nitride (BN), silicon carbide (SiC), beryllium oxide (BeO), potassium nitrate (KNO 3 ), diammonium phosphate (NH 4 H 2 PO 4 ), BaTiO 3 、Pb(Zr,Ti)O 3 (PZT), P 1-x La x Zr 1- y Ti yO 3 (PLZT, 0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -PbTiO 3 (PMN-PT), hafnium dioxide (HfO 2 )、SrTiO 3 SnO 2 、CeO 2 、NiO、CaO、ZrO 2 , SiC and TiO 2 , or a mixture of two or more thereof, but the present disclosure is not limited thereto.

[0143] In one embodiment of the present disclosure, when inorganic particles other than boehmite are also included as inorganic particles, the amount of the inorganic particles also included can be, for example, 20 wt % or more, specifically 15 wt % or less, 10 wt % or less, 5 wt % or less, 1 wt % or less, but the present disclosure is not limited thereto.

[0144] In one embodiment of the present disclosure, the average particle size D of the inorganic particles is 50 It is not limited to a specific range, but may preferably be in the range of 0.01 μm to 2 μm, and specifically 0.5 μm to 1 μm, in order to form a porous coating layer of uniform thickness and ensure optimal porosity.

[0145] In one embodiment of the present disclosure, the binder material may include an acrylic polymer, a PVDF-based polymer, or a mixture thereof.

[0146] Acrylic polymers may include, for example, (meth) acrylic polymers. (Meth) acrylic polymers may include (meth) acrylic acid esters as monomers, and the monomers may include, for example, at least one of butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, ethyl (meth) acrylate, methyl (meth) acrylate, n-propyl (meth) acrylate, isopropyl (meth) acrylate, tert-butyl (meth) acrylate, amyl (meth) acrylate, n-oxyl (meth) acrylate, isooctyl (meth) acrylate, isononyl (meth) acrylate, lauryl (meth) acrylate, and tetradecyl (meth) acrylate.

[0147] In one embodiment of the present disclosure, the acrylic polymer may include styrene-butyl acrylate.

[0148] According to one embodiment of the present disclosure, the acrylic polymer may include, for example, those having a glass transition temperature Tg of 0° C. to 80° C., specifically 20° C. to 60° C., 30° C. to 50° C., 35° C. to 45° C., or 40° C. to 45° C. When the glass transition temperature of the binder material is within the above range, this may have a beneficial effect on the air permeability and adhesive strength of the porous coating layer, but the present disclosure is not limited thereto.

[0149] PVDF-based polymers may include at least one of the following: homopolymers of vinylidene fluoride (i.e., polyvinylidene fluoride), copolymers with monomers that can be copolymerized with vinylidene fluoride, and mixtures thereof. In one embodiment of the present disclosure, monomers may include, for example, fluorinated monomers and / or chloride-based monomers. Non-limiting examples of fluorinated monomers may include at least one of the following: vinyl fluoride; trifluoroethylene (TrFE); chlorofluoroethylene (CTFE); 1,2-difluoroethylene; tetrafluoroethylene (TFE); hexafluoropropylene (HFP); perfluoro (alkyl vinyl) ethers, such as perfluoro (methyl vinyl) ether (PMVE), perfluoro (ethyl vinyl) ether (PEVE) and perfluoro (propyl vinyl) ether (PPVE); perfluoro (1,3-dioxole); and perfluoro (2,2-dimethyl-1,3-dioxole) (PDD).

[0150] In one embodiment of the present disclosure, the PVDF-based polymer may include at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-chlorofluoroethylene (PVDF-CTFE), polyvinylidene fluoride-tetrafluoroethylene (PVDF-TFE) and polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE).

[0151] According to one embodiment of the present disclosure, the PVDF-based polymer may include, for example, those having a glass transition temperature Tg of -80°C to 0°C, specifically -60°C to -20°C, -50°C to -30°C, -45°C to -35°C, or -45°C to -40°C.

[0152] When the glass transition temperature of the binder material is within the above range, this may have a beneficial effect on the air permeability and adhesive strength of the porous coating layer, but the present disclosure is not limited thereto.

[0153] In this specification, the glass transition temperature can be measured by a method commonly used to measure the glass transition temperature of a polymer material, for example, it can be measured using differential scanning calorimetry (DSC) according to ISO 1135762. Specifically, a graph showing the relationship between the temperature and heat flow of a sample that changes with the temperature of the DSC sample can be obtained, and when two extension lines on the graph before and after the slope of the graph changes at a position where the slope of the graph changes sharply are connected, the glass transition temperature can be measured at the intersection with the graph. In this case, the temperature change can be performed by increasing and decreasing the temperature in a single or repeated manner at a constant speed of 0.01°C / min to 100°C / min (e.g., 10°C / min) in the range of -80°C to 500°C.

[0154] According to another aspect of the present disclosure, a method for manufacturing the separator having the above configuration is provided.

[0155] Method for producing a separator for an electrochemical device

[0156] First, according to one embodiment of the present disclosure, the porous polyolefin substrate used in the separator may be manufactured by the following method.

[0157] The method for manufacturing a porous polyolefin substrate may include, for example, the following steps: hot melt extruding a raw material containing a polyolefin resin to obtain a polymer hot melt extrusion product; shaping and stretching the obtained hot melt extrusion product to obtain a polymer sheet; applying a coating solution containing a thermal initiator and a vinyl-containing silane compound to the polymer sheet; and drying and heat-setting the polymer sheet coated with the coating solution. The polyolefin resin includes a polyolefin resin produced using an olefin polymerization catalyst containing chromium.

[0158] First, a raw material including a polyolefin resin produced using an olefin polymerization catalyst including chromium is hot-melt extruded to obtain a polymer hot-melt extrusion product.

[0159] In one embodiment of the present disclosure, for hot melt extrusion, the raw material preferably contains a diluent in addition to the polyolefin resin produced using the olefin polymerization catalyst containing chromium.

[0160] The diluent may include, for example, liquid or solid paraffin oil, mineral oil, wax, soybean oil, which are commonly used to make wet partitions.

[0161] In one embodiment of the present disclosure, the diluent may include a diluent that allows liquid-liquid phase separation from the polyolefin resin, and may include, for example, phthalates such as dibutyl phthalate, dihexyl phthalate, dioctyl phthalate; aromatic ethers such as diphenyl ether, benzyl ether; fatty acids having 10 to 20 carbon atoms such as palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid; aliphatic alcohols having 10 to 20 carbon atoms such as palmityl alcohol, stearyl alcohol; , oleyl alcohol; aliphatic esters in which saturated and unsaturated fatty acids having 4 to 26 carbon atoms in the fatty acid group, or one or two or more fatty acids in which the double bonds of unsaturated fatty acids are replaced by epoxides, are esterified with alcohols having 1 to 8 hydroxyl groups and 1 to 10 carbon atoms, such as palmitic acid monoesters, diesters or triesters, stearic acid monoesters, diesters or triesters, oleic acid monoesters, diesters or triesters, linoleic acid monoesters, diesters or triesters; or a mixture of two or more thereof, but not limited thereto.

[0162] In one embodiment of the present disclosure, based on 100 parts by weight of polyolefin, the diluent may be included in an amount of, for example, 100 parts by weight to 350 parts by weight, or 125 parts by weight to 300 parts by weight, or 150 parts by weight to 250 parts by weight. When the total amount of the diluent satisfies the above numerical range, problems with a large amount of polyolefin, such as low porosity, small pore size, poor connectivity between pores, resulting in significantly reduced permeability, and high viscosity of the polyolefin composition, resulting in increased extrusion load and poor processing, and problems with a small amount of polyolefin, such as poor mixing between polyolefin and diluent, thermodynamic mixing of failure of polyolefin and diluent, and gel formation during extrusion, resulting in fracture and uneven thickness during stretching, may be prevented, but the present disclosure is not limited thereto.

[0163] In one embodiment of the present disclosure, in addition to the polyolefin resin produced using an olefin polymerization catalyst containing chromium and the diluent, the feedstock may also include a polyolefin resin produced using another type of olefin polymerization catalyst such as a Ziegler-Natta catalyst, or an olefin polymerization catalyst containing titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), vanadium (V) or two or more thereof, or any other polymer resin, and the polyolefin resin and the other polymer resin are the same as described above.

[0164] For example, in one embodiment of the present disclosure, the feedstock may further include a polyolefin resin produced by an olefin polymerization reaction using a Ziegler-Natta catalyst.

[0165] According to one embodiment of the present disclosure, a weight ratio of a polyolefin resin produced using an olefin polymerization catalyst containing chromium (Cr-type polyolefin) to a polyolefin resin produced using another type of olefin polymerization catalyst (ZT-type polyolefin) in a raw material may be 1:9 to 9:1, specifically 2:8 to 8:2, 3:7 to 7:3, or 5:5, but the present disclosure is not limited thereto.

[0166] According to another embodiment of the present disclosure, when a ZT type polyolefin is further included in addition to a Cr type polyolefin, the amount of the polyolefin resin produced using the olefin polymerization catalyst containing chromium may be, for example, 10 wt% or more, based on a total of 100 wt% of the raw materials. Specifically, the amount of the polyolefin resin produced using the olefin polymerization catalyst containing chromium may be 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, and / or 99.9 wt% or less, 99 wt% or less, 95 wt% or less, or 90 wt% or less, based on a total of 100 wt% of the raw materials, but the present disclosure is not limited thereto.

[0167] In one embodiment of the present disclosure, the step of obtaining a polymer hot-melt extrusion product may use a single-screw extruder or a twin-screw extruder commonly used in the art, but is not limited thereto.

[0168] Subsequently, the obtained polymer hot-melt extrusion product is shaped and stretched to obtain a polymer sheet.

[0169] In one embodiment of the present disclosure, after extruding the polymer hot melt extrusion product, a cold extrusion product may be formed by casting or calendaring using water cooling or air cooling.

[0170] In one embodiment of the present disclosure, a separator substrate having improved mechanical strength and puncture strength may be provided through the forming and stretching steps.

[0171] In one embodiment of the present disclosure, stretching can be performed sequentially or simultaneously by a roller or tenter process. The stretching ratio can be, for example, 3 times or more, or 5 times to 12 times in each of the vertical and horizontal directions, and the total stretching ratio can be 20 times to 120 times. When the stretching ratio meets the above-mentioned numerical range, this can have a beneficial effect on the thickness uniformity of the separator substrate and the balance characteristics between the vertical and horizontal directions, but the present disclosure is not limited thereto.

[0172] In one embodiment of the present disclosure, the stretching temperature may be changed according to the melting point of the polyolefin resin used and the concentration and type of the diluent, and the present disclosure is not limited thereto.

[0173] Subsequently, the diluent is extracted from the oriented polymer sheet to obtain a porous polymer sheet.

[0174] In one embodiment of the present disclosure, the diluent may be extracted from the oriented sheet using an organic solvent having a high solubility in the diluent and then dried to form a porous sheet.

[0175] The organic solvent is not limited to a specific type and may include those capable of extracting the diluent used, but in terms of extraction efficiency and drying rate, the organic solvent may include methyl ethyl ketone, methylene chloride, hexane.

[0176] In one embodiment of the present disclosure, the extraction method can include any commonly used solvent extraction method, such as dipping, solvent spraying and ultrasonic extraction, used alone or in combination. In one embodiment of the present disclosure, the amount of residual diluent after extraction can preferably be 1 weight % or less. When the amount of residual diluent is within the above range, this can have a beneficial effect on the permeability and mechanical properties of the separator substrate and the efficiency of the manufacturing process, but the present disclosure is not limited thereto. The extraction time and extraction temperature can be changed according to the thickness of the polymer sheet and the type of polymer, and the present disclosure is not limited thereto.

[0177] Subsequently, a coating solution containing a thermal initiator and a vinyl-containing silane compound is applied to the polymer sheet.

[0178] According to one embodiment of the present disclosure, a coating solution containing a thermal initiator and a vinyl-containing silane compound is applied to a porous polymer sheet in which the pores are exposed. As described above, the thermal initiator can activate the terminal vinyl groups in the chain of the polyolefin resin to form free radicals. Therefore, due to the thermal initiator, multiple cross-linked structures can be formed in the polyolefin chain, and the coating solution can penetrate into the fibrils present on the surface of the already formed pores, thereby improving the heat resistance of the separator substrate, but the present disclosure is not limited thereto. In addition, the vinyl-containing silane compound can be included by grafting of a silicon-containing organic group at the activation site of the terminal vinyl group in the chain of the polyolefin resin via a covalent bond. Therefore, the wettability of the separator substrate can be improved, but the present disclosure is not limited thereto.

[0179] In one embodiment of the present disclosure, the thermal initiator and the vinyl-containing silane compound in the coating solution may be included, for example, in a weight ratio of 2: 8 to 8: 2, particularly 3: 7 to 7: 3 or 4: 6 to 6: 4. When the weight ratio of the thermal initiator to the vinyl-containing silane compound is within the above range, the vinyl groups in the chains of the polyolefin resin may be sufficiently activated to cause crosslinking and grafting reactions and improve wettability of the separator substrate, but the present disclosure is not limited thereto.

[0180] In one embodiment of the present disclosure, the coating solution may include a solvent for a thermal initiator and a vinyl-containing silane compound, such as ethanol, propanol, acetone, NMP, DMAC, DMF, water, or a mixture of two or more thereof. In addition, the total solid concentration in the coating solution may preferably be, for example, 5 wt % to 60 wt %, specifically 7 wt % to 40 wt %, to achieve free radical activation of double bonds and improve wettability of the separator substrate, but the present disclosure is not limited thereto.

[0181] In one embodiment of the present disclosure, the coating solution may further include additives generally used to improve specific functions, such as surfactants, oxidation stabilizers, UV stabilizers, charge inhibitors, nucleating agents, if necessary, but the present disclosure is not limited thereto.

[0182] Subsequently, the polymer sheet coated with the coating solution is dried and heat-set to obtain a separator substrate.

[0183] Heat setting is to set the porous film and apply heat to forcibly hold the porous film that tends to shrink, thereby removing residual stress.

[0184] According to the method for manufacturing a separator substrate, a coating solution containing a thermal initiator and a vinyl-containing silane compound can be applied before heat setting, and during heat setting, multiple cross-linked structures can be formed through a cross-linking reaction in the polyolefin chain and / or between the chains through a free radical polymerization reaction mediated by the thermal initiator, and a porous polyolefin substrate based on a polyolefin resin containing multiple silicon-containing organic groups grafted to the ends of the polyolefin chains can be obtained.

[0185] In one embodiment of the present disclosure, the heat setting temperature and time may vary according to the amount of vinyl groups in the polyolefin chain and the composition of the coating solution, and the present disclosure is not limited thereto.

[0186] Subsequently, according to one embodiment of the present disclosure, as described above, the porous coating layer used in the separator may be manufactured by the SRS manufacturing method, the CCS manufacturing method, or any other known method.

[0187] In one embodiment of the present disclosure, the porous coating layer may be manufactured by the following method.

[0188] First, the above-mentioned binder material is dispersed or dissolved in a solvent to prepare a binder dispersion or a binder solution. Subsequently, inorganic particles are added to the binder dispersion or the binder solution and dispersed to prepare a porous coating layer-forming slurry.

[0189] In one embodiment of the present disclosure, according to the type of binder polymer, solvent can serve as the dissolution medium that makes binder polymer dissolve and the dispersion medium that makes binder polymer disperse but does not make binder polymer dissolve.Solvent can include those with solubility parameter similar to the binder polymer used with expectation and low boiling point.In this case, can make uniform mixing and subsequent solvent removal easy.The limiting examples of solvent can include and be selected from the following one or its two or more mixtures: water, acetone, tetrahydrofuran, methylene dichloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP) and hexanaphthene.

[0190] In one embodiment of the present disclosure, inorganic particles can be added after it is ground into a predetermined average particle size, or after inorganic particles are added to a slurry in which a binder polymer is dissolved or dispersed, inorganic particles can be dispersed while utilizing ball milling to grind with the average particle size controlled to a predetermined level. In this case, grinding can be performed for 1 hour to 20 hours, and the average particle size of the ground inorganic particles can be the same as above. Grinding method can include any commonly used method, for example, can include ball milling.

[0191] In one embodiment of the present disclosure, the solid content of the porous coating layer forming slurry may be 5 wt % to 60 wt %, or 30 wt % to 50 wt %. When the solid content of the porous coating layer forming slurry is within the above range, coating uniformity can be easily ensured, and uneven coating and high energy consumption required to dry the flowing slurry can be prevented.

[0192] The method for coating the porous coating on the separator substrate to form a slurry may include any coating method commonly used in the corresponding technical field, such as dip coating, die coating, roller coating, comma coating, micro-gravure coating, blade coating, reverse roller coating, Mayer rod coating, direct roller coating or a combination thereof. In addition, drying can be carried out by any commonly used drying process, such as natural drying and air drying, without limitation.

[0193] Electrochemical Devices

[0194] An electrochemical device according to another aspect of the present disclosure includes a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, and in this case, for the separator, the above-mentioned separator is used.

[0195] In the present specification, a positive electrode, a negative electrode, and an electrode assembly may include those generally used in corresponding technical fields, and a description thereof is omitted.

[0196] According to another aspect of the present disclosure, a secondary battery may be provided by preparing an electrode assembly including a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, placing the prepared electrode assembly in an appropriate case, and injecting an electrolyte solution.

[0197] Hereinafter, the present disclosure will be described in more detail through examples, but the following examples are provided only for illustration, and the scope of the present disclosure is not limited thereto.

[0198] [Preparation of porous polyolefin substrate]

[0199] Preparation Example

[0200] 9kg / hr Cr type polyolefin (DL Chemical, TR570) and 21kg / hr diluent (Kukdong Oil & Chemicals LP350F) as raw materials were fed into an extruder (Korea EM, φ32 twin screw extruder L / D=56) and hot melt extruded at 200°C to obtain a polyolefin hot melt extrusion product. The obtained polyolefin hot melt extrusion product was passed through a T-die, formed into a sheet using a cold casting machine, and biaxially stretched by a tenter type orientator in sequential order by MD stretching and TD stretching to obtain a polyolefin sheet. The MD stretching ratio and the TD stretching ratio were 7 times and 6 times, respectively, and the stretching temperature was MD 115°C, TD 125°C. The diluent was extracted from the oriented polyolefin sheet using dichloromethane to obtain a porous polyolefin sheet.

[0201] Subsequently, a coating solution containing 10 wt % of dicumyl peroxide as a thermal initiator and 20 wt % of vinyltrimethoxysilane as a vinyl-containing silane compound (wetting agent) in an ethanol solvent was applied to one surface of the porous polyolefin sheet.

[0202] Subsequently, the polyolefin sheet coated with the coating solution was dried and heat-set at 128° C. to manufacture a separator substrate. In this case, the average thickness of the obtained separator substrate was 9.0 μm.

[0203] Comparative Preparation Example

[0204] 9 kg / hr ZT type polyolefin (Korea Petrochemical Ind. Co., Ltd., VH035) as a raw material and 21 kg / hr liquid paraffin oil (Kukdong oil & Chemicals LP350F) as a diluent were fed into an extruder (Korea EM, φ32 twin-screw extruder L / D=56) and hot-melt extruded at 200°C to obtain a polyolefin hot-melt extrusion product.

[0205] The obtained polyolefin hot melt extrusion product was passed through a T-die, formed into a sheet using a chill caster, and biaxially stretched by sequentially stretching in MD and TD through a tenter type orienter to obtain a polyolefin sheet. The MD stretching ratio and the TD stretching ratio were 7 times and 6 times, respectively, and the stretching temperatures were 115° C. in MD and 125° C. in TD.

[0206] The diluent was extracted from the oriented polyolefin sheet using methylene chloride to obtain a porous polyolefin sheet, and the porous polyolefin sheet was dried and heat-set at 128° C. to produce a separator substrate. In this case, the average thickness of the obtained separator substrate was 9.0 μm.

[0207] [Evaluation of properties of porous polyolefin substrates]

[0208] Measurement of gel fraction

[0209] First, 0.2 g of the separator substrate sample was placed in a 120-mesh stainless steel sieve, then extracted in trichlorobenzene at 100° C. for 12 hours, and dried in a vacuum oven at 100° C. for 12 hours.

[0210] Subsequently, the weight of the sample remaining in the stainless steel sieve was measured, and the gel fraction was measured according to the following equation: The gel fraction was the average value of the measured values ​​of 3 samples.

[0211] Gel fraction (%) = {(remaining sample weight g) / 0.2 g} × 100

[0212] Measurement of the amount of chromium (Cr), silicon (Si) and aluminum (Al)

[0213] First, the separator substrate sample was reacted and sulfated with sulfuric acid on a hot plate, and the sulfuric acid was removed. Subsequently, the sample was burned in an electric furnace (temperature: 600° C.) for 4 hours to decompose into nitric acid and hydrogen peroxide. Subsequently, the sample was dissolved and when it was clear, it was diluted three times in ultrapure water to prepare a sample for analysis.

[0214] The amounts of chromium (Cr), silicon (Si), and aluminum (Al) in the separator substrate were measured using an inductively coupled plasma mass spectrometer (ICP-MS) (Axiom MC model, Thermo Elemental Ltd, UK).

[0215] When the Ziegler-Natta catalyst is used, aluminum (Al) is present on the separator substrate, and thus the amount of aluminum is detected in order to confirm the use of the Ziegler-Natta catalyst.

[0216] Fracture temperature

[0217] The fracture temperature of the prepared separator substrate was analyzed using a thermal mechanical analyzer (TMA) (TA Instruments, TMA Q400).

[0218] Specifically, a load of 0.01 N was applied to the separator substrate and the degree of deformation was observed while increasing the temperature at a rate of 5° C. / min, and as the temperature increased, the separator substrate contracted and expanded, and the temperature at which it broke was measured as the “fracture temperature”.

[0219] Measurement of the number of spots

[0220] By visually measuring every m 2 The number of spots whose long side length is 50 μm or more.

[0221] Thickness uniformity measurement

[0222] The standard deviation of the thickness was measured using the thickness measured at a total of 100 positions in an area of ​​1 m at intervals of 10 cm in the width direction and 30 m at intervals of 3 m in the length direction of the separator substrate.

[0223] Wettability Measurement

[0224] After dropping a 4 μm droplet of dimethyl carbonate (DMC) on one surface of the separator substrate, the area where the droplet spread was measured. Specifically, the surface of the separator substrate was photographed to obtain an image at a predetermined time after dropping DMC, and the area where DMC spread was measured on the image.

[0225] [Table 1]

[0226]

[0227] [Manufacturing of separator]

[0228] Example 1

[0229] The porous polyolefin substrate according to the Preparation Example was prepared as a separator substrate.

[0230] The porous coating layer was formed by the following W-SRS (water-based SRS) manufacturing method. Specifically, styrene-butyl acrylate (Tg 40° C., particle size (D 50 ) 500nm) and PVDF-HFP copolymer (HFP 5wt%, Tg-40℃, particle size (D 50 )500nm) and boehmite (AlO(OH) as inorganic particles, particle size (D 50)500 nm) were added to water in a weight ratio of 10:10:80 and mixed using a bead mill mixer for about 2 hours to prepare a porous coating-forming slurry.

[0231] The prepared porous coating layer-forming slurry was applied to both surfaces of the prepared porous polyolefin substrate using a bar coater and dried at 60° C. for 10 minutes to obtain a separator having a 3 μm-thick porous coating layer on each of both surfaces of the porous polyolefin substrate.

[0232] Example 2

[0233] The porous polyolefin substrate according to the Preparation Example was prepared as a separator substrate.

[0234] The porous coating layer was formed by the following CCS manufacturing method. Specifically, styrene-butyl acrylate (Tg 40°C, particle size (D 50 )500nm) and boehmite (AlO(OH) as inorganic particles, particle size (D 50 )500 nm) were added to water at a weight ratio of 5:95 and mixed using a bead mill mixer for about 2 hours to prepare a porous coating-forming slurry.

[0235] The prepared porous coating layer-forming slurry was applied to both surfaces of the prepared porous polyolefin substrate using a bar coater and dried at 60° C. for 10 minutes to obtain a separator having a 2 μm-thick porous coating layer on each of both surfaces of the porous polyolefin substrate.

[0236] Comparative Example 1

[0237] A porous polyolefin substrate according to Comparative Preparation Example was prepared as a separator substrate.

[0238] A separator having a 3 μm-thick porous coating layer on each of both surfaces of a porous polyolefin substrate was obtained by the same method as in Example 1, except that aluminum oxide (Al 2 O 3 , particle size (D 50 )500nm) as inorganic particles.

[0239] Comparative Example 2

[0240] A porous polyolefin substrate according to Comparative Preparation Example was prepared as a separator substrate.

[0241] A separator having a 2 μm-thick porous coating layer on each of both surfaces of a porous polyolefin substrate was obtained by the same method as in Example 2, except that aluminum oxide (Al 2 O 3 , particle size (D 50)500nm) as inorganic particles.

[0242] Comparative Example 3

[0243] The porous polyolefin substrate according to the Preparation Example was prepared as a separator substrate.

[0244] A separator having a 2 μm-thick porous coating layer on each of both surfaces of a porous polyolefin substrate was obtained by the same method as in Example 2, except that aluminum oxide (Al 2 O 3 , particle size (D 50 )500nm) as inorganic particles.

[0245] Comparative Example 4

[0246] The porous polyolefin substrate according to the Preparation Example was prepared as a separator substrate.

[0247] A separator having a 2 μm-thick porous coating layer on each of both surfaces of the porous polyolefin substrate was obtained by the same method as in Example 2, except that aluminum hydroxide (Al(OH) 3 , particle size (D 50 )500nm) as inorganic particles.

[0248] [Evaluation of separator characteristics]

[0249] The characteristics of the separator were evaluated by the following methods, and the results are shown in Table 2.

[0250] Evaluation of bond strength

[0251] In order to evaluate the adhesive strength between the porous polyolefin substrate and the porous coating layer, the peel strength was measured by the following method.

[0252] First, the separator to be measured was cut into a size of 15 mm × 100 mm. A double-sided adhesive tape was attached to a glass plate, and the separator was attached so that the surface of the porous coating of the prepared separator adhered to the adhesive tape. Subsequently, the end of the attached separator was mounted on a UTM instrument (LLOYD Instrument LF Plus), and a force was applied at a measurement rate of 300 mm / min at 180° to measure the force required to peel the porous coating from the porous polymer substrate.

[0253] Air permeability

[0254] Air permeability is measured by the Gurley method according to ASTM D726-94. Here, Gurley refers to the resistance to air flow and is measured by a Gurley densometer. The air permeability value represents the air penetration time, that is, 100cc of air at 12.2 inches H 2 The time (in seconds) it takes for a pressure of 0 to pass through a 1 square inch cross-section of the target separator.

[0255] Thermal shrinkage

[0256] The separator to be measured was cut into a size of 50 mm*50 mm, placed between A4 papers, and placed in a 120°C convection oven for 1 hour, then heat treated and the heat shrinkage in the machine direction (MD) and transverse direction (TD) was measured.

[0257] In this case, the heat shrinkage ratio is calculated as [(initial length-length after heat treatment) / (initial length)×100].

[0258] [Table 2]

[0259]

[0260] As can be seen from Table 2 above, it is determined that the separators of Example 1 and Example 2 according to an embodiment of the present disclosure have high bonding strength between the porous polyolefin substrate and the porous coating, while the separators according to Comparative Examples 1 to 4 have low bonding strength between the porous polyolefin substrate and the porous coating.

[0261] In particular, when a porous polyolefin substrate comprising a cross-linked polyolefin resin containing a silicon-containing organic group grafted onto a polyolefin chain and chromium according to the preparation example is used, it is determined that a porous coating layer comprising boehmite (AlO(OH)) as an inorganic particle can significantly improve the bonding strength between the porous polyolefin substrate and the porous coating layer without any particular restriction on the method for forming the porous coating layer. More specifically, it is determined that Comparative Example 3 using aluminum oxide as an inorganic particle has a very low bonding strength between the porous polyolefin substrate and the porous coating layer, and Comparative Example 4 using aluminum hydroxide as an inorganic particle has a very low bonding strength and very low heat resistance due to the low density of aluminum hydroxide.

[0262] Although the present disclosure has been described above with reference to the embodiments and the accompanying drawings, it will be apparent to those skilled in the art that various changes and modifications may be made within the scope of the present disclosure based on the above description.

Claims

1. A separator for an electrochemical device, comprising: a porous polyolefin substrate and a porous coating on at least one surface of the porous polyolefin substrate, wherein the porous polyolefin substrate comprises a cross-linked polyolefin resin, wherein the cross-linked polyolefin resin comprises silicon-containing organic groups grafted onto polyolefin chains, wherein the porous coating layer comprises inorganic particles and a binder polymer, and The inorganic particles include boehmite (AlO(OH)).

2. The separator for an electrochemical device according to claim 1, wherein the porous polyolefin substrate has a gel fraction of 3% to 80%, and wherein a standard deviation (Δd) of thickness measured at at least 100 random points is 0.5 μm or less. 3 . The separator for an electrochemical device according to claim 1 , wherein the adhesive strength between the porous polyolefin substrate and the porous coating layer is 50 gf / 15 mm or more. 4 . The separator for an electrochemical device according to claim 3 , wherein the adhesive strength between the porous polyolefin substrate and the porous coating layer is 70 gf / 15 mm to 95 gf / 15 mm. 5 . The separator for an electrochemical device according to claim 1 , wherein an amount of the boehmite is 80 wt % or more based on the total weight of the inorganic particles.

6. The separator for an electrochemical device according to claim 1, wherein the silicon-containing organic group is a residue derived from a vinyl-containing silane compound, and The vinyl-containing silane compound includes vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, (3-methacryloxypropyl)trimethoxysilane, (3-methacryloxypropyl)triethoxysilane, vinylmethyldimethoxysilane, vinyl-tri(2-methoxyethoxy)silane, vinylmethyldiethoxysilane, or a mixture of two or more thereof. 7 . The separator for an electrochemical device according to claim 1 , wherein the porous polyolefin substrate further comprises chromium (Cr). 8 . The separator for an electrochemical device according to claim 7 , wherein the amount of chromium is 0.1 ppm to 20 ppm. 9 . The separator for an electrochemical device according to claim 1 , wherein the cross-linked structure in the cross-linked polyolefin resin comprises a structure derived as a result of a free radical polymerization reaction between vinyl groups mediated by a thermal initiator. 10 . The separator for an electrochemical device according to claim 9 , wherein the thermal initiator comprises a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

11. An electrochemical device comprising: A positive electrode, a negative electrode, and a separator according to any one of claims 1 to 10 between the positive electrode and the negative electrode.